Mobile Health Technologies - Theories and Applications 2016
DOI: 10.5772/64620
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Diabetes Patient with Mobile Health Technologies

Abstract: Chronic diseases, especially diabetes mellitus, are huge public health burden. Therefore, new health care models for sharing the responsibility for care among health care providers and patients themselves are needed. The concept of empowerment promotes patient's active involvement and control over their own health. It can be achieved through education, self-management, and shared decision making. "ll these aspects can be covered by mobile health technologies, the so-called mHealth. This term comprises mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Despite literature discussing the potential of apps for diabetes self-management (46), specific conclusions for empowerment, lacking empirical evidence, rarely go beyond general overviews (45;47), or are not based on a comprehensive theoretical explication (e.g., 48). Most diabetes-related mHealth projects focusing on empowerment are of applied character and/or do not have much explanatory value (48–50).…”
Section: Diabetes Self-management and Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite literature discussing the potential of apps for diabetes self-management (46), specific conclusions for empowerment, lacking empirical evidence, rarely go beyond general overviews (45;47), or are not based on a comprehensive theoretical explication (e.g., 48). Most diabetes-related mHealth projects focusing on empowerment are of applied character and/or do not have much explanatory value (48–50).…”
Section: Diabetes Self-management and Empowermentmentioning
confidence: 99%
“…For example, Park et al (51) found that empowerment could occur when T2DM patients shared information or received social support using their mobile devices, when patients realized the outcomes of mHealth supported activities, or when the mobile devices were used for improved activity planning. Krošel et al suggest that mHealth is “(…) offering different means for introduction of the concept of empowerment into patients’ everyday life” (47, p. 35), yet conclude it still plays a minor role in diabetes self-management, with apps lacking perceived benefit and ease of use.…”
Section: Diabetes Self-management and Empowermentmentioning
confidence: 99%
“…Theoretically all aspects of empowerment including education, self-management, and shared decision-making can be covered by mobile health technologies, so-called mHealth [51]. For example, a mobile-phone-based tool to capture and visualize food intake was effective in empowerment of young people with type 1 diabetes with their diet [52].…”
Section: The Effects Of Empowerment Therapy In Type 1 Diabetesmentioning
confidence: 99%
“…Examples include Life in Control, Medios Technologies AI assistant to detect diabetic retinopathy, mySugr etc. [ 95 795 796 797 ] Diabetes technologies are meant for saving the time and better short term and long term outcomes. Choice should depend on the knowledge, infrastructure and the need.…”
Section: Mplementationmentioning
confidence: 99%